University and business relations: connecting the knowledge economy - Metcalfe, Stan (Springer Netherlands, 2010)
It is commonplace to say that the modern economy is knowledge based but a moment’s reflection points to the vacuity of this notion. For all economies are knowledge based and could not be otherwise. The question is rather how is one kind of knowledge based economy to be distinguished from another? This essay proposes that the answer may lie in three directions: (1) in terms of the variety of knowledge that is engaged; (2) in terms of the processes by which the production of knowledge is organised, and its corollary the resources devoted to knowledge production and dissemination; and, (3) in terms of the purposes to which knowledge is put. In respect of each of these dimensions, the rise of the modern university as a custodian of knowledge in Western economy and society has been of central importance; but universities are not alone in this role, a wide range of other agencies, private firms, public research laboratories for instance play an important role in defining a knowledge economy and have done so increasingly since the turn of the nineteenth century—a first indication of the systemic dimensions of a modern knowledge economy.